2004
DOI: 10.1177/145749690409300307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fibrin Sealant Combined with Fibrinolysis Inhibitor on Reducing the Amount of Lymphatic Leakage after Axillary Evacuation in Breast Cancer

Abstract: Potentially, fibrin sealant combined with fibrinolysis inhibitor might be used for the treatment of post- axillary evacuation lymphorrhea and seroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 10 publications
0
24
0
4
Order By: Relevance
“…In this situation, fibrin sealants have demonstrated no significant effect on the incidence of postoperative seromas [20][21][22], the volume of drainage output [22], or the time to drain removal [20]. Other studies have reported that the volume of fluid aspirated from seromas in the fibrin treatment group was significantly greater than the volume in the control group [23,24].…”
Section: Clinical Impact Of Postoperative Seromamentioning
confidence: 98%
“…In this situation, fibrin sealants have demonstrated no significant effect on the incidence of postoperative seromas [20][21][22], the volume of drainage output [22], or the time to drain removal [20]. Other studies have reported that the volume of fluid aspirated from seromas in the fibrin treatment group was significantly greater than the volume in the control group [23,24].…”
Section: Clinical Impact Of Postoperative Seromamentioning
confidence: 98%
“…A reduction in postoperative drainage and hospital stay were observed following use of fibrin glue, but it did not affect delayed seroma formation [49]. However, the use of fibrin glue or peri-operative and postoperative administration of a fibrinolysis inhibitor does not reduce seroma formation [50]. …”
Section: Obliteration Of Dead Spacementioning
confidence: 99%
“…Bei verschiedenen plastisch-chirurgischen Operationen wurde daher bereits der präventive Einsatz von Gewebeklebern zur Vermeidung von Seromen untersucht, so z. B. bei Axilladissektion [13], Gesichtstraffung [14] und Lidplastik [12].…”
Section: Fibrinkleber Und Serombildung Nach Abdominoplastikunclassified
“…Mustonen et al [13] fanden in einer prospektiven Studie über den Gebrauch von Fibrinklebern bei Axilladissektionen eine einheitliche Inzidenz von Seromen, jedoch in einer quantitativ deutlich geringeren Ausprägung bei den verklebten Achselhöhlen. Ebenfalls signifikant positive Auswirkungen von Fibrinklebern zeigten sich bei der Bildung von Seromen bei Gesichtstraffungen [14] und der Hebung von M.-latissimus-dorsi-Lappenplastiken [9].…”
Section: Introductionunclassified